RASIONALISASI KRAMA DESA ADAT DLOD TUKAD BATUBULAN MENETAP DI TANAH PEKARANGAN DESA - Pratiwi, Ni Komang Rahma Tri; Nugroho, Wahyu Budi; Kamajaya, Gede; Pramestisari, Nyoman Ayu Sukma (JURNAL ILMIAH SOSIOLOGI: SOROT; Vol 4 No 1 (2024): JISSOROT, 2024)
ABSTRACT This research aims to explain and analyze the rationalization of the traditional village habits of Dlod Tukad Batubulan who live in the village yard with the burden of fatherly responsibilities in the midst of today's modern, practical life. The method used in this research is a qualitative approach with a descriptive-explanatory type. The theory used in this research as a scalpel in analyzing the phenomena that occur is Max Weber's theory of social action. The results of research in the field reveal that there are four rationalities that underlie the reasons for the manners of the Dlod Tukad Batubulan traditional village choosing to settle in the village yard with the burden of paternal responsibility in the traditional village, which consists of value rationality, instrumental rationality, traditional actions and affective actions. Furthermore, the results of this research reveal that the Dlod Tukad Batubulan Traditional Village, which is a new traditional village in Bali, does not fully use traditional authority arrangements in carrying out its government, especially in solving problems related to today's modern life.   Key words: Traditional village, rationalization, village land.